2016
DOI: 10.21475/ajcs.2016.10.10.p7761
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth and genetic polymorphism in glyphosate-resistant sourgrass (Digitaria insularis L. Fedde)

Abstract: Weed herbicide resistance has been a challenge in agriculture. The objective of this study was to detect sourgrass (Digitaria insularis (L.) Fedde) glyphosate-resistant plants and to evaluate the growth and polymorphism rate between the resistant and susceptible biotypes, as a subsidy for the integrated management of species. An experiment was conducted primarily for the detection of weed resistance using increasing doses of glyphosate to generate a dose-response curve. Then, an experiment consisting of eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
(22 reference statements)
2
9
0
1
Order By: Relevance
“…Similar results were found by Martins et al (2016), who evaluated the growth of D. insularis and found faster development for resistant plants, which reached the flowering stage first than glyphosate-susceptible plants. In addition, seed-propagated sourgrass emits inflorescence between 63 and 70 days after sowing (Machado et al, 2006), which is much slower when compared to that from vegetative propagation-between 21 and 50 DAP (Table 3).…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Similar results were found by Martins et al (2016), who evaluated the growth of D. insularis and found faster development for resistant plants, which reached the flowering stage first than glyphosate-susceptible plants. In addition, seed-propagated sourgrass emits inflorescence between 63 and 70 days after sowing (Machado et al, 2006), which is much slower when compared to that from vegetative propagation-between 21 and 50 DAP (Table 3).…”
supporting
confidence: 86%
“…This resulted in the selection of glyphosate-resistant weeds (Koger and Reddy, 2005). There are several reports of glyphosate-resistant sourgrass in Brazil (Carvalho et al, 2012;Barroso et al, 2015;Galeano et al, 2016;Martins et al, 2016;Gazola, 2017). Sourgrass populations resistant to fenoxaprop-p-ethyl and haloxyfop-p-methyl herbicides have recently been reported in the State of Mato Grosso (Heap, 2018), which is a major concern to producers, as ACCase inhibitors are the main herbicides for controlling postemergent D. insularis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sourgrass plants have high variability. Martins et al (2016) evaluated random primers and found that the DNA of glyphosate-resistant and susceptible sourgrass plants presented a variation of 56.6%. This is a highly competitive plant with great infestation potential and fast and aggressive growth, which develops well in poor and acidic soils and has high seed germination percentages (above 90%) (Mondo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%